2021
DOI: 10.1186/s40621-021-00339-5
|View full text |Cite
|
Sign up to set email alerts
|

Firearm purchasing and firearm violence during the coronavirus pandemic in the United States: a cross-sectional study

Abstract: Background Firearm violence is a significant public health problem in the United States. A surge in firearm purchasing following the onset of the coronavirus pandemic may have contributed to an increase in firearm violence. We sought to estimate the state-level association between firearm purchasing and interpersonal firearm violence during the pandemic. Methods Cross-sectional study of the 48 contiguous states and the District of Columbia from Jan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 36 publications
6
75
1
Order By: Relevance
“…During this time, Americans began to purchase firearms at an extraordinary rate. In the first four months of the pandemic, 4.3 million more firearms were purchased in the U.S than expected based on historical trends, an 85% increase [3] . In addition, the United States experienced heightened racial tensions in 2020 with several high-profile police shootings.…”
Section: Introductionmentioning
confidence: 98%
“…During this time, Americans began to purchase firearms at an extraordinary rate. In the first four months of the pandemic, 4.3 million more firearms were purchased in the U.S than expected based on historical trends, an 85% increase [3] . In addition, the United States experienced heightened racial tensions in 2020 with several high-profile police shootings.…”
Section: Introductionmentioning
confidence: 98%
“…A study of trends from January through May 2020 found a strong state-level association between the size of the increase in firearm purchasing and the size of the subsequent increase in firearm violence (Schleimer et al 2020 ). By July, however, as violence increased in response to seasonal trends, social unrest, and other factors, that association was no longer detectable for firearm violence overall, but persisted for intimate partner violence (Schleimer et al 2021 ).…”
Section: Violencementioning
confidence: 99%
“…However, such measures have significantly impacted the mental preference and behavioral pattern of individuals, which has led to further changes in the disease spectrum (1,2). It has been proven that during this pandemic, there exists an increasing trend in interpersonal violence-related trauma and traffic-related trauma due to anxiety, irritability, and cancellation of public transportation (3)(4)(5)(6). The pandemic has also significantly disrupted scheduled medical activities, through the redeployment of more healthcare resources to COVID-19 patients and addition of COVID-19 screening for infection control before treatment (7,8).…”
Section: Introductionmentioning
confidence: 99%